Surveyed dermatologists are less likely to curette invasive squamous cell carcinoma in solid organ transplant recipients - Kathleen M. Nemer, MD; Tyler M. Bauman, MD; M. Laurin Council, MD; Eva A. Hurst, MD (Wolters Kluwer, 2020)
Background: The risk of squamous cell carcinoma (SCC) is increased in solid organ transplant recipients (OTRs), and preferential treatment modalities vary among clinicians. Objectives: The purpose of this study was to survey dermatologists regarding practice patterns for electrodesiccation and curettage (EDC) of SCC in OTRs and nontransplant patients. Methods: An 18-question survey was sent to dermatologist members of the International Transplant Skin Cancer Collaborative, Association of Professors of Dermatology, and American College of Mohs Surgery. Differences in EDC practice patterns for treatment of SCC in OTRs and nontransplant patients were evaluated. Results: Dermatologists in this study (N = 227) were more likely to treat SCC with EDC in nontransplant patients (67.4%) than in OTRs (48.0%; P = .0003).Dermatologists who perform EDC in both groups (n = 108) were unlikely to use EDC on the H-zone of the face; they were more likely to EDC tumors on non-H-zone areas of the face and neck in nontransplant patients compared to OTRs (P = .0007). Dermatologists were more likely to use EDC over surgery in nontransplant patients compared to OTRs with the following demographics: dementia or psychiatric disease (P = .04), multiple medical comorbidities (P = .03), or anticoagulation medications (P = .02). Conclusions: In OTRs with SCC, 48% of clinicians would consider EDC. The main factors that affect the decision to perform EDC include tumor location and patient comorbidities. Keywords: Squamous cell carcinoma, Solid organ transplant recipient, Electrodesiccation and curettage, Survey, Practice patterns